Analysis on micro-mixing enhancement through a constriction under time periodic electroosmotic flow - Lim, Chun Yee (2013)
Numerical analyses of the recently proposed micro mixer based on periodic electroosmotic flow through a constriction were conducted. The validity and accuracy of the numerical model developed were verified experimentally. The model allows the prediction of operating parameters such as alternating current (AC) amplitude and frequency for optimum mixing. For accurate simulations of flow behavior such that optimum operating conditions could be determined, the electromigration effect of charged fluorescent dye added to the fluid stream must be considered. This effect, which is generally ignored, can be incorporated in the convection diffusion equation. Important factors that govern the mixing efficiency of the mixer, such as the contact area between the two fluids and the amplitude of fluid interface oscillation were quantified based on experimental and numerical results. Detailed error analyses were performed to investigate the sensitivity of simulation results to the variability of constriction width, diffusion coefficient, and fluorescein ion mobility. This also provides an understanding on the fabrication requirement for efficient mixing.